Fusobacterium nucleatum elicits subspecies-specific responses in human neutrophils - Muchova, Maria; Kuehne, Sarah A.; Grant, Melissa M.; Smith, Peter P.; Nagi, Malee; Chapple, Iain L. C.; Hirschfeld, Josefine (Frontiers in Cellular and Infection Microbiology, 2024)
Fusobacterium nucleatum as a Gram-negative anaerobe plays a key bridging role in oral biofilms. It is involved in periodontal and extraoral diseases, the most prominent being colorectal cancer. Five subspecies are recognised: animalis, fusiforme, nucleatum, polymorphum and vincentii. Subspecies interact with neutrophils constantly patrolling tissues to remove microbial intruders. Neutrophil antimicrobial activities include generation of reactive oxygen species (ROS), formation of neutrophil extracellular traps (NETs) and release of cytokines and neutrophil enzymes. Subspecies-specific differences in immunogenicity have previously been observed in a neutrophil-like cell line but were not investigated in human neutrophils. Additionally, neutrophil responses to planktonic and biofilm-grown F. nucleatum have not been studied to date. The aims of this study were to compare the immunogenicity of planktonic and biofilm-grown F. nucleatum and to investigate potential differences in human neutrophil responses when stimulated with individual F. nucleatum subspecies. Human neutrophils isolated from peripheral blood were stimulated with planktonic and biofilm-grown F. nucleatum subspecies. Generation of ROS and NET formation were quantified by luminescence and fluorescence assays, respectively. Secretion of cytokines (IL-1β, TNF-α, IL-6, IL-8), neutrophil elastase and matrix metalloproteinase-9 was quantified by enzyme-linked immunosorbent assay (ELISA). Neutrophil responses showed biofilm-grown bacteria induced a significantly higher total and intracellular ROS response, as well as shorter time to total ROS release. Biofilm-grown F. nucleatum led to significantly lower IL-1β release. We found significant differences among individual subspecies in terms of total, intracellular ROS and extracellular superoxide. Subspecies polymorphum stimulated the highest mean amount of NET release. Amounts of cytokines released differed significantly among subspecies, while no differences were found in lysosomal enzyme release. Immunogenicity of F. nucleatum in human neutrophils is highly subspecies-specific in vitro with regard to ROS release and cytokine production. Understanding subspecies-specific immunogenicity of F. nucleatum may facilitate the discovery of novel therapeutic targets in F. nucleatum-mediated diseases.